Improving landscape architectural problem solving: integrating giscience and technology educational objectives in landscape architecture curricula - Kersey, David Nathaniel (Kansas State University, 2008)
The profession of landscape architecture is involved in understanding, designing and, or, implementing relationships between social and natural systems within a spatial-temporal context as defined in discipline literature and the 2005 Landscape Architecture Body of Knowledge (LABOK) study. The LABOK outlines core competencies of the profession and fundamental body of knowledge expected from graduates of Landscape Architecture Accreditation Board (LAAB) accredited degree programs. Geographic Information Science (GIScience) is a emerging field aimed at spatial temporal problem solving and has been defined as, “a multi disciplinary research enterprise that addresses the nature of geographic information and the application of geospatial technologies to a basic scientific question” (DiBiase, 5, 2006; Goodchild, 1992). The Geographic Information Science & Technology Body of Knowledge (GIS&TBOK) (DiBiase, 121, 2007) outlines educational objectives for the emerging field of GIScience and serves as the resource for course and curriculum planning for academic and professional programs. This study investigated where intersections exist between the spatial temporal problem solving discipline of landscape architecture and emerging field of GIScience based on the respective Body of Knowledge studies. The three phased study: 1) determined overlapping relationships between the LABOK and GIS&T BOK, 2) analyzed overlaps for their ability to help first professional degree landscape architecture programs achieve LAAB curriculum accreditation, and 3) employed a case study method to illustrate how overlaps between the LABOK and GIS&T BOK and relevant to LAAB curriculum accreditation requirements influence curricula development at Kansas Sate University. The study established 887 relationships between the two respective Bodies of Knowledge, of which, 717 were found capable of helping achieve LAAB curriculum accreditation. The study presents key areas of intersection and overlap between LABOK and GIS&T, and provides a framework for integration of GIS&T educational objectives within first professional landscape architecture degree curriculums, in a manner to achieve LAAB curriculum accreditation.
Keywords: Landscape architecture; GIScience; Body of knowledge; Landscape Architecture (0390)